Miltefosine enhances the fitness of a non-virulent drug-resistant Leishmania infantum strain. (8th November 2018) - Eberhardt, Eline; Bulté, Dimitri; Van Bockstal, Lieselotte; Van den Kerkhof, Magali; Cos, Paul; Delputte, Peter; Hendrickx, Sarah; Maes, Louis; Caljon, Guy
Abstract: Objectives: Miltefosine is currently the only oral drug for visceral leishmaniasis, and although deficiency in an aminophospholipid/miltefosine transporter (MT) is sufficient to elicit drug resistance, very few naturally miltefosine-resistant (MIL-R) strains have yet been isolated. This study aimed to make a detailed analysis of the impact of acquired miltefosine resistance and miltefosine treatment on in vivo infection. Methods: Bioluminescent versions of a MIL-R strain and its syngeneic parental line were generated by integration of the red-shifted firefly luciferase PpyRE9 . The fitness of both lines was compared in vitro (growth rate, metacyclogenesis and macrophage infectivity) and in BALB/c mice through non-invasive bioluminescence imaging under conditions with and without drug pressure. Results: This study demonstrated a severe fitness loss of MT-deficient parasites, resulting in a complete inability to multiply and cause a typical visceral leishmaniasis infection pattern in BALB/c mice. The observed fitness loss could not be rescued by host immune suppression with cyclophosphamide, whereas episomal reconstitution with a wild-type MT restored parasite virulence, hence linking parasite fitness to MT mutation. Remarkably, in vivo miltefosine treatment or in vitro miltefosine pre-exposure significantly rescued MIL-R parasite virulence. The in vitro pre-exposed MIL-R promastigotes showed a longer and more slender morphology, suggesting an altered membrane composition. Conclusions: The profound fitness loss of MT-deficient parasites most likely explains the low frequency of MIL-R clinical isolates. The observation that miltefosine can reverse this phenotype indicates a drug dependency of the MT-deficient parasites and emphasizes the importance of resistance profiling prior to miltefosine administration.